Pós-tratamento de efluente de instituição de ensino superior por ultrafiltração e adsorção para reúso - Pavan, Maritania Morgan (2016)
The population growth, the technological and industrial advances cause an increase of the water consumption, in what way over the years, it has been studied alternatives that aim to the sustainable use, minimizing losses and waste so that future generations can enjoy this feature . In this way, it can be considered the reuse of domestic sewage as an efficient alternative, with an intention to its sustainability, reusing the treated effluent for less noble purposes than human consumption. The sewage coming from the Effluent Treatment Station (ETS), generally have a residual concentration of organic load, requiring additional steps to obtain effluent quality capable of reuse. The aim of this study was to use the process of Ultrafiltration (UF) followed by adsorption in column of granular activated carbon, acting as a polishing step for reuse purposes. The sanitary effluent used was the ETE / FUPF which undergoes by a biological treatment followed by a disinfection system by sodium hypochlorite, requiring a tertiary treatment step in order to achieve the reuse patterns in toilets. The effluent passed through UF pre-optimized process conditions, and it has been subjected to the adsorption process in a fixed bed column with activated coal. During this process, it was evaluated the effect of pH, temperature, bed height and rate of application in relation to the color of the effluent, resulting inremoval of 95% DQO, 90% of color, 100% turbidity and 74% the organic matter present in theeffluent treated by ETE / FUPF. Finally, long term trials were conducted to obtain the breakthrough curves comparing the parameters of the treated effluent standards for reuse. It wasobserved that the UF process associated with adsorption on beds of coal enabled between 15 and 20 cm, using flow rates of 5 ml / min, it was able to remove up to 95% of residual color, reaching the standards for reuse in toilets.